Peningkatan Pemahaman Konsep Dasar Peta melalui Pemanfaatan Media Interaktif pada Siswa Kelas IV Yayasan Al-Hidayah - Muhammad Hafiz Ermawan; Anggili Pratama; Aurora Febriani Br. Barus; Ferra Mutia Sari; Putri Febrianti Purba; Selpiana Dongoran; Yasria Idaman Fersi Waruwu (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
Understanding the concept of a base map is a crucial skill in elementary school science and social studies. However, many students still face challenges, particularly in recognizing symbols, understanding scale, and reading location-related information. This study aims to explain how the use of interactive learning media can improve the understanding of fourth-grade students at the Al-Hidayah Foundation regarding the concept of a base map. The method used involved direct observation in learning activities with interactive maps, where students actively participated by pointing out country locations, utilizing symbols, and identifying regional boundaries. The results of the observations showed that interactive media was able to overcome cognitive and visual problems experienced by students previously, because the direct and participatory presentation of maps made it easier for them to understand. In addition, active participation in practical activities increased students' motivation and curiosity. Therefore, it can be concluded that the use of interactive learning media has a positive impact on improving the understanding of the concept of a base map among elementary school students, while strengthening the relevance of more practical science and social studies learning.